Estrogenic control of germ cell differentiation in medaka: independence of early sex dimorphism from zygotic estrogen and receptor signaling - Sakai-Yamada, Yuta; Myosho, Taijun; Kayo, Daichi; Kanda, Shinji; Kobayashi, Tohru (Frontiers in Endocrinology, 2026)
BackgroundEstrogen signaling is essential for ovarian differentiation in vertebrates, but its developmental onset and specific roles during early gonadogenesis remain unclear. In medaka (Oryzias latipes), the first morphological sex difference appears as a higher germ cell number in XX compared with XY embryos before hatching. Recently, we demonstrated that zygotically synthesized estrogen was dispensable for early germ cell sex difference but essential for subsequent oocyte meiotic progression and ovarian fate maintenance. Nevertheless, whether these phenomena depend on maternal estrogen or zygotic estrogen signaling mediated by nuclear estrogen receptors (nEsrs) is unknown.ObjectiveTo clarify the receptor-level requirement of estrogen signaling, we generated esr1/2a/2b triple knockout (ΔnEsrs) medaka using CRISPR/Cas9 genome editing. By comparing these receptor-deficient mutants with our previous ligand-deficient (Δcyp19a1a/1b double knockout) model, we aimed to determine whether estrogen signaling is involved in the establishment of the early germ cell number difference or acts later to control meiotic progression and ovarian maintenance.MethodsWe established ΔnEsrs medaka using CRISPR/Cas9 and analyzed gonadal histology, germ cell kinetics, and expression of steroidogenic enzyme genes, sex differentiation-related genes, and oocyte-specific expressed genes during early development.ResultsΔnEsrs mutants displayed normal early germ cell number and sex-specific differences at hatching (0 dph). At 10 dph, diplotene oocytes were markedly reduced, accompanied by significant downregulation of oocyte-specific genes, figa, 42sp50, as well as cyp19a1a and foxl2 mRNA. However, ΔnEsrs did not cause feedback regulation on other hypothalamus-pituitary-gonad (HPG) axis gene expression.ConclusionOur results demonstrate that estrogen signaling, both at the ligand and receptor levels, is dispensable for establishing the early germ cell sex difference but essential for subsequent oocyte meiotic progression and ovarian fate maintenance. This establishes a two-step estrogenic control model, redefining the developmental timing of estrogen action during the early phase of gonadal differentiation in vertebrate reproduction.